2023
DOI: 10.3389/fphar.2023.1153991
|View full text |Cite
|
Sign up to set email alerts
|

Lenvatinib resistance mechanism and potential ways to conquer

Abstract: Graphical AbstractIn this review, we summerized the absorption, distribution, metabolism, excretion of lenvatinib in clinic. The lastest mechanism and potential approches to overcome resistance caused by lenvatinib were supplied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 154 publications
0
5
0
Order By: Relevance
“…Meanwhile, resistance to and side effects of MTKIs are common problems in cancer treatment ( 4 ). The drug resistance mechanisms of sorafenib and lenvatinib includes epithelial-mesenchymal transition, DNA damage, ferroptosis, RNA modification, cytokine overexpression, translational modification, and self-target signal pathway ( 21 , 22 ). While using MTKIs like sorafenib or lenvatinib, it is important to monitor for adverse events and adjust doses or discontinue the drug as needed.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, resistance to and side effects of MTKIs are common problems in cancer treatment ( 4 ). The drug resistance mechanisms of sorafenib and lenvatinib includes epithelial-mesenchymal transition, DNA damage, ferroptosis, RNA modification, cytokine overexpression, translational modification, and self-target signal pathway ( 21 , 22 ). While using MTKIs like sorafenib or lenvatinib, it is important to monitor for adverse events and adjust doses or discontinue the drug as needed.…”
Section: Discussionmentioning
confidence: 99%
“…However, LVN is unaffected by pH-elevating agents, race and renal function. 18 High-fat diet, 19 aging, 20 impaired liver function and hepatoprotective drugs 21,22 could also influence steady-state blood concentrations of orally administered LVN, as shown in Figure 1.…”
Section: The Clinical Pharmacological Character Of Lvn and Antitumor ...mentioning
confidence: 99%
“…Regardless of other elements determining the pharmacokinetics of LVN, the actual plasma concentration is the most valuable indicator for patients, and it cannot be replaced by other indirect indicators. 18 However, the relative information is limited and inconsistent. Data from the patients with unresectable HCC revealed that the mean trough plasma concentration was approximately 30-40 ng/mL, regardless of the dose of LVN.…”
Section: The Clinical Pharmacological Character Of Lvn and Antitumor ...mentioning
confidence: 99%
See 2 more Smart Citations